Correlation of ANXA1 expression with drug resistance and relapse in bladder cancer - Yu, Shuliang (e-Century Publishing Corporation, 2014)
Objective: To investigate the expression of annexin a1 (ANXA1) in adriamycin-resistant human bladder cancer cell line (pumc-91/ADM) compared with the parental cell line (pumc-91) and its relevance to the drug resistance of bladder cancer, as well as explore the relevance of ANXA1 in recurrent bladder cancer tissues as pertinent to relapse. Methods: qRT-PCR and Western blot were implemented to research the level of ANXA1 in two cell lines (pumc-91/ADM and pumc-91). Immunohistochemistry was applied to explore ANXA1 expression in bladder cancer tissues of different intervals of relapse. The association of ANXA1 with clinicopathological parameters was analyzed. Results: The expression of ANXA1 was downregulated in drug-resistant cell line pumc-91/ADM compared to pumc-91. The bladder cancer tissues recurring two years later exhibited higher ANXA1 levels. ANXA1 expression level was positively correlated with T stage, while it was not connected with histological grade strongly. The expression level and influencing factors of ANXA1 in recurrent tissues of bladder cancer were clarified for the first time. Conclusion: ANXA1 may become a promising marker to predict the recurrence and drug resistance of bladder cancer and provide guidance for surveillance.